Peer Tutoring with Liveworksheets in Accounting Classrooms: Tutor Sebaya dengan Liveworksheets dalam Pembelajaran Akuntansi - Solihati, Essy; Suherman, Uman; Kusumaryono, Suyato (Indonesian Journal of Innovation Studies, 2025)
Background: Accounting education in secondary schools often faces low student engagement and limited competence. Specific background: Traditional teaching tends to be passive, while interactive methods such as peer tutoring and digital worksheets are underexplored in accounting. Knowledge gap: Few studies have combined peer tutoring with interactive platforms like Liveworksheets for this subject. Aims: This study investigates the role of peer tutoring supported by Liveworksheets in fostering student activity and competence in accounting. Results: A quantitative experimental design with 71 participants showed significant increases in learning activity, supported by paired sample t-tests and N-Gain scores. Posttest results revealed higher achievement compared to pretest scores, with student feedback indicating strong positive responses to the digital integration. Novelty: This research demonstrates how combining peer tutoring with interactive digital worksheets promotes both social collaboration and autonomous practice in accounting classrooms. Implications: The findings suggest that such blended approaches can be applied not only in accounting but also in other theoretical subjects to enrich active learning and improve student competence. Highlights Student activity improved after peer tutoring combined with digital worksheets Accounting competence increased significantly based on posttest and N-Gain results Positive student feedback confirmed the interactive and collaborative learning process Keywords: Peer Tutoring, Liveworksheets, Student Activity, Accounting Learning, Student Competence